THE STATUS OF THE LAND-BASED AND OFFSHORE AQUACULTURE SYSTEMS IN CEBU, PHILIPPINES - Corrales, Christine M; Delan, Gloria G; Rica, Rachel Luz V; Piquero, Alfonso S; Monte, Irene A (Journal of Agriculture and Technology Management, 2015)
Development of aquaculture systems are growing due to increasing human population and its demand for aquaculture products. This brought environmental concerns on the effects of aquaculture systems on water quality and nearby ecosystems. In order to determine whether water quality can still support marine life and suitable for aquaculture purposes, assessment of eight aquaculture systems in Cebu was conducted. Water samples were collected within the aquaculture systems and fishpond outlets. These were brought to a water laboratory for analysis of BOD, Total Coliform, Nitrate, Phosphate, Ammonia and Total Suspended Solids. Water temperature, pH, D.O, conductivity, TDS and salinity were measured in-situ. Results showed that the pH within fish cages and brackish water fishponds exceeded the standard limit while dissolve oxygen falls below the minimum standard limit. However, these values falls within the desirable, optimum and ideal growth of species cultured. The total coliform count was found highest in freshwater ponds which also exceeded the standard limit. Sedimentation was higher in aquaculture systems than in fishpond outlets due to waves exposure, currents and fishermen activities. Biophysical assessment showed fair condition of live hard corals, high fish diversity, moderate fish density and high fish biomass in Badian fish cages. Poor seagrass cover was observed in Carmen fish cages. Mangrove species were found nearby fishponds while trees, palms and grasses were observed in upland fishponds. This study revealed that water quality of most fishpond outlets and aquaculture systems were within the water classification of DAO 34, 1990 and found to have a minimal effect on the environment particularly on water quality and the cultured species.